Origins of stereoselectivity in the trans Diels-Alder paradigm. - Paton, R; Mackey, J; Kim, W; Lee, J; Danishefsky, S; Houk, K (2010)
The regioselectivity and stereoselectivity aspects of the Diels-Alder/radical hydrodenitration reaction sequence leading to trans-fused ring systems have been investigated with density functional calculations. A continuum of transition structures representing Diels-Alder and hetero-Diels-Alder cycloadditions as well as a sigmatropic rearrangement have been located, and they all lie very close in energy on the potential energy surface. All three pathways are found to be important in the formation of the Diels-Alder adduct. Reported regioselectivities are reproduced by the calculations. The stereoselectivity of radical hydrodenitration of the cis-Diels-Alder adduct is found to be related to the relative conformational stabilities of bicyclic radical intermediates. Overall, the computations provide understanding of the regioselectivities and stereoselectivities of the trans-Diels-Alder paradigm.